Pengaruh Media Audio Visual terhadap Kemampuan Bahasa Reseptif Anak Usia Dini - Yulianti, Eti; Nurunnisa, Rita (IKIP Siliwangi, 2025)
Receptive language ability refers to the capacity to understand or receive messages conveyed by others. It is a critical aspect of language development, as it significantly influences a person’s overall language skills. Based on observations conducted at Karunia Jaya Kindergarten, the receptive language skills of children aged 5–6 years were found to be suboptimal. This was evident in their difficulty understanding lessons delivered by the teacher. Therefore, appropriate stimulation through learning media is necessary, one of which is the use of audio-visual media. However, this type of media had not previously been utilized due to limited school facilities. The purpose of this study was to examine the effect of audio-visual media on the receptive language skills of children aged 5–6 years. The research employed a pre-experimental design. The subjects were 15 children aged 5–6 years. Data were collected through observation over the course of eight meetings. Data were analyzed using parametric statistical methods, with hypothesis testing conducted via a t-test using the SPSS version 25 application. The analysis results showed a calculated t-value of 6.790 and a t-table value of 1.753, meaning that tcount > ttable; thus, the alternative hypothesis (Ha) was accepted. This indicates that the use of audio-visual media has a significant effect on the receptive language skills of children aged 5–6 years. Kemampuan bahasa reseptif adalah kemampuan menerima pesan yang disampaikan orang lain. Bahasa reseptif sangat penting karena akan mempengaruhi kemampuan berbahasa seseorang. Berdasarkan observasi yang telah dilakukan di TK Karunia Jaya bahwa kemampuan bahasa anak usia 5-6 tahun belum tercapai dengan baik, ditunjukan dengan kesulitan anak untuk memahami pembelajaran yang disampaikan oleh guru, sehingga diperlukan stimulasi melalui media pembelajaran, salah satunya adalah penggunaan media audio visual. Media audio visual ini termasuk media yang belum digunakan untuk pembelajaran karena kurangnya sarana yang ada di sekolah. Tujuan penelitian ini untuk mengetahui pengaruh media audio visual visual terhadap kemampuan bahasa reseptif pada anak usia 5-6 tahun. Metode penelitian ini menggunakan ekperimen dengan jenis pra eksperimental. Subjek penelitian adalah 15 anak usia 5-6. Pengumpulan data menggunakan observasi selama delapan kali pertemuan. Analisis data menggunakan statistic parametik dengan uji hipotesis menggunakan Uji-t menggunakan bantuan aplikasi SPPS versi 25. Hasil analisis pada penelitian menunjukkan thitung sebesar 6,790 dan ttabel 1,753, artinya thitung > ttabel atau sama dengan Ha diterima yaitu adanya pengaruh penggunaan media audio visual terhadap kemampuan bahasa reseptif anak usia 5-6 tahun.